Sistem Cerdas Reservasi Kamar Hotel Berbasis Analytical Hierarchy Process (AHP) Untuk Mempercepat Proses Pemilihan Kamar - Stevani Isabella; Yuthsi Aprilinda (Universitas Bandar Lampung (UBL), 2012)
Widara Asri Hotel is a Company engaged in the field of hospitality in the city of Bandar Lampung. Currently Widara Asri Hotel is not only engaged in the hospitality Sudak but progessed to the culinary field. Rapid technological developments make Widara Asri Hotel need to acipt to the use of these technologies. One technology was adapted by Widara Asri Hotel is internet technology that can be used to asisst the process of booking a hotel room.This thesis will decribe and explain the use of analytical hierarch process method to help speed up the selection of hotels room. AHP is used to scale down the ratio of multiple pairwise comparisons that are discrete or continous. Comparison of these pairs can be obtained through actual measurements and measurements of the relative degree of preference, or the interest or the feelings.